Seed productivity of Trigonella species - І. М. Бобось (Plant Varieties Studying and Protection)
The article unveils the seed potential of fenugreek species to provide routine supply of methi leaf in the conditions of Ukrainian Forest-Steppe. The fenugreek species have have a wide range of morphological and economical characteristics variability that affect their seed production. A high productivity of dry seeds is inherent to fenugreek species at early spring sowing (10.04), as for this date the yield of dry seeds of blue fenugreek amounted to 0.4 t per ha, that of fenugreek hay – 2.0 t / ha, with mass of 1000 seeds, respectively, 0.71 and 9.7 gr. To obtain a spicery called «mushroom grass» the use of fenugreek hay is considered as a promising direction (Greek hay, Shambhala, hay fenugreek) along with scheduling the sowing for early spring (4.10) and late spring (25.04–15.05) , which would enable the development of greatest herbage volume and higher yield of mature seed (0.9–2.0 t / ha). Another prospective line of development is to use blue fenugreek (fenugreek blue) as a green manure and nectar bearing crop, with the sowing scheduled for spring (4.10) and late spring (25.04–15.05).